(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Poisoning is the fourth most common unintentional cause of death, after vehicle crashes, burns and drowning, with the prevalence of poisoning being 0.5 per 100,000 people. Aims and Objectives: To study incidence, clinical course and management in childhood poisonings, and to identify the common substances causing it, to analyze various complications and mortality in childhood poisoning. Materials and methods: This is prospective observational study carried out in all patients of childhood poisoning under the age of 12 years and fulfilling the inclusion criteria admitted in the tertiary health care center in South Gujarat. Results: The study constituted majority of the patients (51.11%) under the age of 5 years with Male predominance. The commonest route was oral ingestion (88.88%) with most common agent responsible was Unknown solution (51.11%) followed by Acid Ingestion (8.88%) and Turpentine (6.66%). Anxiety (51.1%%) was the predominant clinical feature followed by vomiting (44.4%). 8.8% patients needed ventilator care. In the present study, fatality rate was 2.2%. Conclusion: The Picture of childhood poisoning found in our study was different from various clinical studies in case of substances causing it.